Early Response of Primary Care Practices to COVID-19 Pandemic. (March 2022) - Keppel, Gina; Cole, Allison M.; Ramsbottom, Mary; Nagpal, Stuti; Hornecker, Jaime; Thomson, Claire; Nguyen, Viet; Baldwin, Laura-Mae
Introduction: The emergence of the COVID-19 pandemic and subsequent public health mitigation strategies resulted in rapid and significant changes to delivery of primary care. The field of primary care faced an unprecedented dual challenge of providing routine care to patients while ensuring patient and staff safety and managing patients with a highly transmissible disease. This study describes how a diverse group of primary care practices addressed these challenges at the start of the COVID-19 pandemic, in Spring 2020. Methods: A cross-sectional electronic survey of representatives from primary care practices in the WWAMI region Practice and Research Network (WPRN). Survey topics included clinical workforce, operations, and use of telemedicine in the first 3 months of the COVID-19 pandemic. Results: To safely manage patients with COVID-19 symptoms all clinics modified operations; 81.3% diverted patients with respiratory symptoms to a telemedicine evaluation, 68.8% diverted these patients to be seen in-person at another location, and 75% made in-clinic changes to maintain safety. The set of operational changes employed by clinics was diverse. To continue to provide routine patient care, all clinics employed telemedicine. Over 80% of clinics had never used telemedicine prior to March 2020. Conclusions: A diverse group of primary care clinics all rapidly implemented a variety of operational adaptations to address patient needs and maintain patient and staff safety at the onset of the COVID- 19 pandemic. Telemedicine, together with other measures, provided critical pathways for maintaining delivery of care.